2012
DOI: 10.4236/ijnm.2012.12002
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Recovery of Manganese using <i>Staphylococcus Epidermidis</i>

Abstract: Manganese minerals are widely distributed throughout the globe. The most important industrial uses of Mn are in the manufacture of steel, non-ferrous alloys, carbon-zinc batteries and some chemical reagents. Microbial recovery of manganese from low grade manganese ores using bioleaching was investigated in this paper. A bacterial strain, Staphylococcus epidermidis (MTCC-435) was collected from microbial type culture collection, IMTECH Chandigarh and used for the experiment. The experimental results for bioleac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…All the isolates showed visible growth up to 500 mM of Mn in the form of MnO 2 supplemented on agar plates. The exceptional ability of bacterial isolates to adapt ad tolerate high concentration of Mn isolated from Mn rich environments has been already reported and established . The bacterial strain MSB 11 showed a maximum solubilisation efficiency of 96.7% while MSB 5, MSB 2, and MMR 1 showed an efficiency of 95, 40, and 48.5%, respectively.…”
Section: Resultsmentioning
confidence: 87%
“…All the isolates showed visible growth up to 500 mM of Mn in the form of MnO 2 supplemented on agar plates. The exceptional ability of bacterial isolates to adapt ad tolerate high concentration of Mn isolated from Mn rich environments has been already reported and established . The bacterial strain MSB 11 showed a maximum solubilisation efficiency of 96.7% while MSB 5, MSB 2, and MMR 1 showed an efficiency of 95, 40, and 48.5%, respectively.…”
Section: Resultsmentioning
confidence: 87%
“…(Das et al 2012b). A range of hydrometallurgical techniques from low-grade ores are investigated and developed for the recovery of Mn (Youcai et al 2014).…”
Section: Recovery Of Mnmentioning
confidence: 99%
“…increase in concentration increases the acid leaching efficiency. The result suggested that oxalic acid have greater leaching capacity than citric acid due to its affinity to bind with Mn and act as the reducing agent by providing H + ion [2]. Oxalic acid has high affinity toward Mn and form Mn-oxalate complexes which leach out manganese from the ore [2].…”
Section: Effect Of Citric Acid On Manganese Leachingmentioning
confidence: 99%
“…The common chemical forms of manganese dioxide found naturally are +2 and +4 [1]. The oxides and peroxides of manganese are used for manufacturing metal alloys to increase hardness and for enhancement of alloy to be corrosion resistance and as a desulfurizing, deoxidizing element in various industrial processes [2,3]. Manganese plays an important role in steel production, preparation of dietary additives, chemical production, in battery cells industry [4,5].…”
Section: Introductionmentioning
confidence: 99%